Contested histories and contested land claims: traditional authorities and the Fast Track Land Reform programme in Zimbabwe, 2000–2017. Issue 159 (2nd January 2019) - Dande, Innocent; Mujere, Joseph
ABSTRACT: This article analyses conflicts among traditional authorities over ancestral lands, and boundaries during and in the aftermath of Zimbabwe's Fast Track Land Reform programme (FTLRP). It argues that the FTLRP gave a fresh impetus to conflicts over land and boundaries among traditional authorities as they sought to recast their authority into areas from which they were displaced during the colonial period. It further argues that land claims in the post-FTLRP period were often entangled with contestations over history and legitimacy as rival groups made use of oral traditions and archives to bolster their claims. Most of these struggles over land ended up being decided in the country's court system. Overall, the article argues that struggles over land claims in the post-FTLRP period have largely ended up being struggles over versions of the history of land ownership and colonial displacements.